Leveling up?: an inter-neighborhood experiment on parochialism and the efficiency of multi-level public goods provision - Gallier, Carlo; Goeschl, Timo (Journal of economic behavior & organization, 2019)
Many public goods can be provided at different spatial levels. Evidence from social identity theory and in-group favoritism raises the possibility that when higher-level provision is more efficient, subjects’ narrow concern for local outcomes could undermine efficiency. Building on the experimental paradigm of multi-level public good games and the concept of “neighborhood attachment,” we conduct an artefactual field experiment with over 600 participants in a setting conducive to routine parochial behavior. In an inter-neighborhood intra-region design, subjects allocate an endowment between a personal, a local, and a regional public good account. The between-subjects design crosses two treatment dimensions: One informs subjects that the smaller local group consists of members from their own neighborhood, while the other varies the relative productivity at the two public goods provision levels. We find evidence for parochialism, but contrary to our hypothesis, parochialism does not interfere with efficiency: The average subject responds to a change in relative productivities at the local and regional levels in the same way, whether they are aware of their neighbors’ presence in the small group or not. The results even hold for subjects with above-median neighborhood attachment and subjects primed on neighborhood attachment.